2019
DOI: 10.1080/2162402x.2018.1560919
|View full text |Cite
|
Sign up to set email alerts
|

Cancer vaccines: designing artificial synthetic long peptides to improve presentation of class I and class II T cell epitopes by dendritic cells

Abstract: Lang (2019) Cancer vaccines: designing artificial synthetic long peptides to improve presentation of class I and class II T cell epitopes by dendritic cells, OncoImmunology, 8:4, e1560919,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In addition, CD4 + T cells also exhibit direct antitumor effector function ( 57 ). Therefore, the artificial elongation of tumor-associated CD8 + Tcell epitopes or the application of multivalent long peptides comprising at the same time CD4 + and CD8 + T cell epitopes displays promising attempts to improve the efficacy and clinical outcome of peptide vaccination ( 58 , 59 , 60 , 61 , 62 , 63 ). The enhanced induction of T cell responses with long vaccine peptides could also be explained by the fact that exact epitopes bind directly to HLA class I molecules of any somatic cell and thus also to nonprofessional antigen-presenting cells (APCs) without further processing, which could then lead to suboptimal T cell priming and induce T cell tolerance ( 51 , 64 , 65 ).…”
Section: Antigen Selection—the Devil Is In the Detailsmentioning
confidence: 99%
“…In addition, CD4 + T cells also exhibit direct antitumor effector function ( 57 ). Therefore, the artificial elongation of tumor-associated CD8 + Tcell epitopes or the application of multivalent long peptides comprising at the same time CD4 + and CD8 + T cell epitopes displays promising attempts to improve the efficacy and clinical outcome of peptide vaccination ( 58 , 59 , 60 , 61 , 62 , 63 ). The enhanced induction of T cell responses with long vaccine peptides could also be explained by the fact that exact epitopes bind directly to HLA class I molecules of any somatic cell and thus also to nonprofessional antigen-presenting cells (APCs) without further processing, which could then lead to suboptimal T cell priming and induce T cell tolerance ( 51 , 64 , 65 ).…”
Section: Antigen Selection—the Devil Is In the Detailsmentioning
confidence: 99%
“…Recently SLPs derived from MELOE-1 melanoma antigen have been developed from Class I and Class II epitopes separated by a cathepsin protease-sensitive linker ( 62 ). Cathepsins are key proteases in dendritic cells involved in antigen presentation ( 63 , 64 ), and it was found that the composition and size of the Cathepsin-sensitive linker had a significant impact on the presentation of the CD4 + and CD8 + T cell epitopes.…”
Section: Designing Peptide-based Cancer Vaccinesmentioning
confidence: 99%
“…Cathepsins are key proteases in dendritic cells involved in antigen presentation ( 63 , 64 ), and it was found that the composition and size of the Cathepsin-sensitive linker had a significant impact on the presentation of the CD4 + and CD8 + T cell epitopes. Of the linker sequences tested, LLSVGG showed the strongest immunogenicity ( 62 ). Mouse studies to evaluate SLPs in the prime-boost immunisation strategy using LLSVGG-based vaccine showed a strong CD8 + T cell response, but a lower CD4 + compared to human PBMC tests, which could produce a less well-rounded response, and shows the epitope sensitivity differences between mice and human models ( 62 ).…”
Section: Designing Peptide-based Cancer Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal peptide length for therapeutic cancer vaccines has been identified in preclinical and clinical studies. Short peptides of ∼ 8-11 amino acids (a.a.) are the typical CD8 + T-cell epitopes while long peptides of ∼ 15-32 a.a. contain both CD8 + and CD4 + Tcell epitopes (6,7). Neoantigenic epitopes can be predicted based on their sequence, expression, proteasome cleavage, peptide abundance, MHC-binding affinity and other physiochemical and structural features of peptide-MHC complexes.…”
Section: Introductionmentioning
confidence: 99%